Institutul de teorie și critică literară G. Călinescu, Bucureşti - Cofan, Aluniţa (Studia Romanica Posnaniensia, 2014)
We are trying in the following phenomenological approach to go on with our description concerning the grotesque in Romanian literature. In the first part of our work, we will make a short and diachronic review of the most important writings belonging to Romanian authors from the XIX-th century till the first decade of the XX-th century. It is then when a mysterious and shy Romanian writer, called URMUZ, gave birth to a few but influential literary pages of the absurd and the grotesque. In the second part of our work we will analyze the distinguishing traits of his ten works of prose through the mirror of the grotesque. This ignored Romanian writer was baptized “a new Alfred Jarry”, although he never had heard about this French author and never read about Ubu. The hidden influence of Urmuz unknowingly modernized the concept of literarity.